Genetic divergence among cultivars of cowpea - Oliveira, Francisco José de; Filho, Clodoaldo José da Anunciação; Bastos, Gerson Quirino; Reis, Odemar Vicente dos (Pesquisa Agropecuaria Brasileira, 2003)
This work aimed to determine the genetic divergence among cowpea cultivars [Vigna unguiculata (L.) Walp.] when grouped in a multivariate analysis concerning to select superior parents. So 16 cowpea cultivars were used from the germplasm bank of the Centro de Ciências Agrárias of the Universidade Federal do Ceará, in Brazil. The data were accomplished in complete randomized blocks, with six blocks, 16 treatments and three cultivar checks. The total area of experimental plots was 24 m2 and the net area was 16 m2, displayed in four rows, plants were spaced about 1.0 x 0.5 m with two plants in each plot. The phenotypic data were estimated from five competitive plants as casual samples on two central rows of each replicate. Breeding among the groups I [TVx-337-3F and Vita-4 (TVu 1977-OD)] and II (Bengala and V-4 Alagoas) may be the direct way to obtain new more productive cultivars because these groups are the most geneticaly divergent. The characters that contributed most to genetic divergence were the medium length of the plants (36.80%) and weight of 100 seeds (19.21%).